The Mitigating Effect of Phentermine and Topiramate on Weight Regain after Roux-en-Y Gastric Bypass Surgery - Istfan, Nawfal W. (Obesity (Silver Spring), 2020)
OBJECTIVE: Weight regain (WR) after Roux en-Y Gastric Bypass surgery (RYGB) starts to occur two years after surgery, ultimately affecting at least 25% of patients. A limited number of studies have evaluated the impact of anti-obesity medications (AOM) on this phenomenon. METHODS: We reviewed the electronic medical records (EMR) of 1196 patients who had RYGB between 2004 and 2015. WR was evaluated by comparing each patient’s weight during subsequent post-operative office visits to nadir weight (lowest weight after RYGB, n=760), taking into consideration the interval during which WR occurred. Patients who were prescribed AOM and came to follow-up visits were classified as adherent users, while those who missed their follow-up visits were considered non-adherent. We used linear mixed model, Cox regression, and generalized equation estimator to determine the impact of AOM on WR trajectory, hazards ratio for time to event, and odds ratio for repeated event occurrence, respectively. RESULTS: Despite lack of a unified protocol for using AOM, the three statistical models converged to show that phentermine and topiramate, used individually or in combination, can significantly reduce WR after RYGB. CONCLUSIONS: Phentermine and topiramate are effective in mitigating WR after RYGB. Further studies are needed to help ascertain optimal use of AOM after bariatric surgery.